Integrating Mycorrhizal Fungi into Orchid Reintroduction: Case Studies, Challenges, and Future Directions - Dissanayake, E. J. M. Samadhi Kavindya; Jayawardana, H.A.S. Dimuthu Ruwan (Ecological Questions, 2026)
Orchid reintroduction: transplanting propagated orchids into natural or restored habitats is a growing conservation strategy to counter population decline and extinction. However, many efforts have overlooked a critical biological requirement: the reliance of orchids on orchid mycorrhizal fungi (OMF) for seed germination, growth, and survival. Without these fungal partners, restored populations often fail to establish or persist. This review explores how integrating OMF into reintroduction strategies improves outcomes across species, regions, and ecological contexts. Drawing on selected case studies from six biogeographic regions, the study highlights the importance of fungal specificity, source, and ecological matching in shaping reintroduction success. It shows that symbiotic propagation, site selection based on fungal compatibility, and sustained monitoring all contribute to higher survival and reproduction rates. However, major challenges remain, including the technical and financial difficulties of isolating and identifying compatible fungal partners, limited long-term monitoring, and insufficient research on field-based fungal management and inoculation in current efforts. To address these gaps, the review proposes an integrated approach that combines scientific, institutional, and community-based actions. Ensuring broader access to fungal resources, building local capacity, and embedding OMF in conservation planning will be key to making orchid reintroduction more ecologically effective and globally equitable.